Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Pada Pokok Bahasan Sistem Periodik Unsur Terhadap Hasil Belajar Siswa Kelas X SMA Negeri 1 Dampelas - Rahmi, Sitti; Said, Irwan; Solfarina, Solfarina (Jurnal Akademika Kimia, 2014)
Learning on teacher centered learning chemistry, causing the interest and creativity of the students do not develop. This condition contributes to the low of students learning outcomes. Students learning outcomes will be better is students experience for themselves what really happened. Therefore we need a method of teaching which is one oriented to students. This study uses a model of cooperative learning TSTS which is one method of teaching. The purpose of this study is to determine the effect of the application of the cooperative learning model TSTS on the subject of the periodic table of the learning outcomes of students of class X SMA Negeri 1 Dampelas. The study population was all students in the class X SMA Negeri 1 Dampelas academic year 2012/2013 consisting of six classes. The study sample consisted of two classes, namely class XA 32 students as the experimental class and the class XF 32 students as the class control are determined by purposive sampling. Results of analysis of data obtained for the mean score on the experiment class X1 = 76.50 with a standard deviation = 12.18 and the control class X2 = 57.81 with a standard deviation = 16.26. Based on the hypothesis testing results obtained tcounting = 5.21 and ttable = 2.00 at Î± = 0.05. In this case H1 is accepted and Ho is rejected, because tcounting is in the rejection of Ho. It can be concluded that the application of cooperative learning model TSTS on the subject of periodic system of elements had a positive effect on learning outcomes of students of class X SMA Negeri 1 Dampelas.